My big fat Greek wedding - Wilson, Rita.; Hanks, Tom.; Goetzman, Gary.; Vardalos, Nia, 1962-; Zwick, Joel.; Corbett, John, 1961-; Kazan, Lainie; Constantine, Michael; Carides, Gia, 1964-; Mandylor, Louis, 1966-; Meisler, Bess.; Martin, Andrea, 1947-; et al. (New York : HBO Home Video, 2003)
Toula is a quiet, devoted daughter in a big, crazy Greek family. Working in her father's restaurant, she hides behind her family and keeps the world at a distance. One day at the restaurant she finds herself pouring coffee for a man who inspires her to change her life - and the way she sees the world ... forever.
Originally produced as a motion picture in 2002.
Special features: widescreen (1.85:1) and full screen (1.33:1) presentations; audio commentary by stars Nia Vardalos, John Corbett and director Jeol Zwick; cast and crew biographies.
Director of photography, Jeffrey Jur ; editor, Mia Goldman ; music, Chris Wilson, Alexander Janko ; costume designer, Michael Clancy ; production designer, Gregory Keen.
Nia Vardalos, John Corbett, Lainie Kazan, Michael Constantine, Gia Carides, Louis Mandylor, Bess Meisler, Andrea Martin, Joey Fantone.
MPAA rating: PG.
DVD, 2.0 Dolby digital, Region 1 encoding.
Keywords: Man-woman relationships -- Drama; Weddings -- Drama; Greek American women -- Drama; Films for the hearing impaired; Feature films; Comedy films